2022
DOI: 10.3390/diagnostics12123220
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Active T-Cell Mediated Kidney Rejection as a Clinically Significant Type of Allograft Loss?

Abstract: The purpose of this article is to assess the present knowledge about chronic active (CA) T-cell mediated rejection (TCMR) of a kidney. In the research authors review current Banff diagnostic criteria used in kidney rejection, focus on their possible future evolution, and investigate the role of currently available molecular methods that could be implemented into the diagnostic scheme. Research also points out previously and currently available treatment methods applied to CA TCMR and takes into account possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…This local expression of IDO1 can contribute to creating an immunosuppressive micro-environment within the transplanted organ. This immunosuppressive environment is believed to be beneficial for promoting graft tolerance and reducing the risk of rejection [29,62]. Given IDO1's role in immune regulation and its potential as both a marker for rejection and an immunosuppressive factor, researchers have explored IDO1-targeted therapies for improving cancer outcomes [63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…This local expression of IDO1 can contribute to creating an immunosuppressive micro-environment within the transplanted organ. This immunosuppressive environment is believed to be beneficial for promoting graft tolerance and reducing the risk of rejection [29,62]. Given IDO1's role in immune regulation and its potential as both a marker for rejection and an immunosuppressive factor, researchers have explored IDO1-targeted therapies for improving cancer outcomes [63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…As CA TCMR is a newly described term, there is a lack of clear guidelines for the management of the ailment. Studies have shown that some researchers hesitate whether CA TCMR should be treated or even diagnosed [49]. In 2017, more than 90% of cooperating clinical centers diagnosed CA TCMR and treated the ailment with immunosuppressive medications including steroids in more than 80% of cases.…”
Section: Chronic Active Tcmr-treatmentmentioning
confidence: 99%
“…There is still a need for large, randomized studies where patients would be treated with different immunosuppressive agents and combinations of those medications to work out an ideal scheme for CA TCMR treatment. Even though some clinical research has already been conducted, the results are questionable and uncertain [49].…”
Section: Chronic Active Tcmr-treatmentmentioning
confidence: 99%